2021
DOI: 10.1021/acs.langmuir.1c01096
|View full text |Cite
|
Sign up to set email alerts
|

Capillary-Driven Rise of Well-Wetting Liquid on the Outer Surface of Cylindrical Nozzles

Abstract: Well-wetting liquids exiting small-diameter nozzles in the dripping regime can partially rise up along the outer nozzle surfaces. This is problematic for fuel injectors and other devices such as direct-contact heat and mass exchangers that incorporate arrays of nozzles to distribute liquids. We report our experimental and numerical study of the rising phenomenon for wide ranges of parameters. Our study shows that the interplay of three dimensionless numbers (the Bond number, the Weber number, and the Ohnesorge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…We also approximate v ηε,0 in the H 2 -norm by C 4+γ functions v βηε,0 , satisfying (33), and replace (34…”
Section: Lemma 32 (Entropy Inequality)mentioning
confidence: 99%
See 2 more Smart Citations
“…We also approximate v ηε,0 in the H 2 -norm by C 4+γ functions v βηε,0 , satisfying (33), and replace (34…”
Section: Lemma 32 (Entropy Inequality)mentioning
confidence: 99%
“…Thin liquid films flowing down a vertical fibre have attracted many interests in the past decades due to their importance in a variety of engineering applications, including heat and mass exchangers, thermal desalination, and vapor and CO 2 capturing [32,43,42,44,31]. These liquid films are fundamentally driven by Rayleigh-Plateau instability and gravity modulation, spontaneously exhibiting complex interfacial instability and pattern formation [24,25,33,28].Previous experimental works have found that the downstream flow dynamics and pattern formation highly depend on the flow rate, fibre radius, liquid properties, and inlet geometries. Specifically, three typical flow regimes have been extensively studied [22,9,29,14,41].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thin liquid films flowing down a vertical fibre have attracted many interests in the past decades due to their importance in a variety of engineering applications, including heat and mass exchangers, thermal desalination, and vapor and CO 2 capturing [27,28,[35][36][37]. These liquid films are fundamentally driven by Rayleigh-Plateau instability and gravity modulation, spontaneously exhibiting complex interfacial instability and pattern formation [20,21,24,29].…”
Section: Introductionmentioning
confidence: 99%
“…Droplet generation has been utilized in various applications, such as 3D printing 3 , electrosprays 4 , and bioengineering 5 . Droplet formation is performed by passive 6 or active 7 methods, which differ in the absence or presence of an external force. Electrical 8 , magnetic 9 , and acoustic 10 forces have been the most external stimuli in the active methods.…”
Section: Introductionmentioning
confidence: 99%